Tim: An Effective Method for Data Timeliness Evaluation in Engineering Data Transmission - Lan, Xinyuan; Han, Chao (2025 International Conference on Computer Science, Technology and Engineering (ICCSTE), 2025)
In the field of engineering data transmission, data timeliness represents a crucial dimension for measuring data quality, which directly impacts the accuracy and effectiveness of engineering decision-making. Based on the characteristics of engineering data transmission scenarios, this paper proposes the data timeliness evaluation problem, and designs a data timeliness evaluation algorithm called Tim. Tim constructs a data transmission time model and combines the characteristics of key nodes such as data generation, transmission, and reception to quantitatively evaluate the timeliness of data. And Tim uses an adaptive BKD-Tree indexing structure to store and query data efficiently. Experimental results demonstrate that the Tim algorithm can accurately and effectively assess the timeliness of engineering data, and Tim algorithm is efficient under real-time streaming compared with traditional methods.